2013
DOI: 10.1021/ma3026089
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Inclusion Polymerization of Acrylonitrile in Urea Canals: Toward Synthesis of Completely Isotactic Polyacrylonitrile with Controlled Molecular Weight

Abstract: Completely isotactic polyacrylonitrile (meso/meso triad >99%) has been synthesized successfully by radiation-induced inclusion polymerization of acrylonitrile in urea canals. The long-lived nature of the growing radical species and the linear dependence of molecular weight on conversion were observed. The molecular weight distribution of product polymers was relatively narrow (<1.5). The results indicate that the dual control of the molecular weight and the tacticity for inclusion polymerization of acrylonitri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…The MMD of the polymer product was relatively narrow (the polydispersity coefficient is less than 1.5). The results show that double control -MM and tact is simultaneously observed, which, according to the authors of [49], is due to polymerization involving urea. Varying the conditions of polymerization showed that for the synthesis of a fully isotactic PAN, the following conditions must be ensured at the same time: (1) mixing of AN and urea before the start of gamma irradiation,…”
Section: Df Grishin Sa Stakhi Id Grishinsupporting
confidence: 52%
“…The MMD of the polymer product was relatively narrow (the polydispersity coefficient is less than 1.5). The results show that double control -MM and tact is simultaneously observed, which, according to the authors of [49], is due to polymerization involving urea. Varying the conditions of polymerization showed that for the synthesis of a fully isotactic PAN, the following conditions must be ensured at the same time: (1) mixing of AN and urea before the start of gamma irradiation,…”
Section: Df Grishin Sa Stakhi Id Grishinsupporting
confidence: 52%
“…PAN synthesized through free radical polymerization has an atactic structure; and the isotactic-rich PAN can be obtained by g-ray radiant polymerization in channel complexes of urea. [13][14][15] The neighboring nitrile group on the isotactic units creates conditions favoring the cyclization. 16,17 Coleman et al 18 concluded that the distribution of the tactic placements of the polymer chain limited the cyclization degree, and this result was further confirmed by a computer simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Almost completely isotactic polyacrylonitrile (the proportion of meso-triadiads is > 99%), as well as copolymers of AN, were successfully synthesized by Chinese chemists [49] under conditions of radiation-induced polymerization of acrylonitrile in the presence of urea. In this case, the main signs of "live" controlled polymerization were observed, including the linear dependence of the MM polymer on conversion.…”
Section: Df Grishin Sa Stakhi Id Grishinmentioning
confidence: 99%